The Variables and Invariants in the Evolution of Logic Optical Lithography Process - Qiang Wu (Journal of Microelectronic Manufacturing, 2019)
Photolithography has been a major enabler for the continuous shrink of the semiconductor manufacturing design rules. Throughout the years of the development of the photolithography, many new technologies have been invented and successfully implemented, such as image projection lithography, chemically amplified photoresist, phase shifting mask, optical proximity modeling and correction, etc. From 0.25 μm technology to the current 7 nm technology, the linewidth has been shrunk from 250 nm to about 20 nm, or 12.5 times. Although imaging resolution is proportional to the illumination wavelength, with the new technologies, the wavelength has only been shrunk from 248 nm to 134.7 nm (193 nm immersion in water), less than 2 times. Would it mean that the imaging performance has been continuously declining? Or we have yet fully utilized the potential of the photolithography technology? In this paper, we will present a study on the key parameters and process window performance of the image projection photolithography from 0.25 μm node to the current 7 nm node.